2021
DOI: 10.3390/nu13124511
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of in Utero Ramadan Exposure: A Systematic Literature Review

Abstract: Health outcomes of in utero Ramadan exposure have been reported in a systematic literature review; however, the available literature on long-term effects were not fully covered. Our study aims to specifically review the long-term outcomes of in utero Ramadan exposure. We searched for original research articles analyzing any long-term outcome of in utero Ramadan exposure, excluding maternal and perinatal outcomes. Sixteen studies from 8304 non-duplicate search results were included. Most studies suggest negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Sixteen studies were included. 47 Most studies suggest negative consequences from in utero Ramadan exposure on health and economic outcomes later in adulthood. Higher under-five mortality rate, higher mortality under three months and one year, shorter stature, lower BMI, increased incidence of vision, hearing, and learning disabilities, lower mathematics, writing, and reading scores, as well as a lower probability to own a home were associated with Ramadan exposure during conception or the first trimester of pregnancy.…”
Section: Highlights Of the Year's Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen studies were included. 47 Most studies suggest negative consequences from in utero Ramadan exposure on health and economic outcomes later in adulthood. Higher under-five mortality rate, higher mortality under three months and one year, shorter stature, lower BMI, increased incidence of vision, hearing, and learning disabilities, lower mathematics, writing, and reading scores, as well as a lower probability to own a home were associated with Ramadan exposure during conception or the first trimester of pregnancy.…”
Section: Highlights Of the Year's Literaturementioning
confidence: 99%
“…There was no difference in anthropometric measurements of newborn children among both groups Two systematic reviews addressed the impact of RF on maternal and fetal health. 47,48 First, research on any longterm outcome of in utero Ramadan exposure was reviewed, excluding maternal and perinatal outcomes. Sixteen studies were included.…”
Section: Effects Of Rf On Maternal and Fetal Healthmentioning
confidence: 99%
“…A part of the literature on the health implications of Ramadan during pregnancy mainly finds associations among those for whom Ramadan during pregnancy occurs in early pregnancy [ 16 ]. Our finding that fasting rates are highest in the first pregnancy trimester might partly explain these previous findings, as some studies use intent-to-treat designs in which Ramadan exposure is measured as the occurrence of a Ramadan during pregnancy rather than via actual fasting.…”
Section: Discussionmentioning
confidence: 99%
“…Estimated rates of fasting among pregnant Muslims range from 54% in the Netherlands to 87% in Pakistan and Singapore and 99% in Bangladesh [ 4 – 7 ]. While the literature on Ramadan fasting during pregnancy and birth outcomes has remained inconclusive [ 8 ], various studies demonstrated that being born in the months after a Ramadan is predictive of worse later-life cognitive and physical health outcomes among Muslims, including symptoms of pulmonary disease, coronary heart disease and type 2 diabetes, increased disability rates, and worse performance in school and on the job market [ 9 16 ]. It is generally assumed that maternal intermittent fasting is the driver of the associations with offspring health.…”
Section: Introductionmentioning
confidence: 99%
“…Among the several risk factors for infertility [ 14 ], gestational exposure to endocrine disruptors, such as bisphenol A (BPA), in combination with HFD may lead to impaired spermatogenesis in F1 and F2 offspring [ 15 ], supporting evidence on the transgenerational inheritance of reproductive disorders as well as of metabolic diseases [ 16 , 17 , 18 ]. With this in mind, studies aiming to unravel the long-term effects of maternal nutrition [ 19 ] may help to further elucidate the relevance and the mechanisms through which gestational nutrients can program metabolic and reproductive functions later in life, as well as in offspring.…”
mentioning
confidence: 99%